2016
DOI: 10.1002/bkcs.10839
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Hemolytic Activity of Stapled Heptapeptide Dimers

Abstract: To improve the antimicrobial activity of the hydrocarbon‐stapled amphipathic heptapeptide helix identified from our previous study, we prepared a series of its dimeric analogs using several different linkers. All of these dimers showed a significant increase in antimicrobial activity although their hemolytic activity was also largely increased. One particular analog bearing a proline linker displayed notably low hemolytic activity compared to others, indicating that the conformational characteristics of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Peptide 3PR3-X showed the highest selectivity index. The results demonstrate that linker flexibility plays a key role in differentiation between hemolytic and antimicrobial activity in doubly-stapled antimicrobial peptide dimers [ 39 ].…”
Section: Hydrocarbon Stapled Antimicrobial Peptidesmentioning
confidence: 99%
“…Peptide 3PR3-X showed the highest selectivity index. The results demonstrate that linker flexibility plays a key role in differentiation between hemolytic and antimicrobial activity in doubly-stapled antimicrobial peptide dimers [ 39 ].…”
Section: Hydrocarbon Stapled Antimicrobial Peptidesmentioning
confidence: 99%
“…The net positive charge and the distribution of charged residues is important for the initial binding step as well as the selectivity with the negatively charged membrane of bacteria species [ 160 ], thus, too high cationic density can cause the reversed effects: less potent antimicrobial activity but more hemolytic activity [ 161 ]. In fact, most of the natural AMPs have the net charge from +2 to +10 [ 9 ] and some studies suggested the optimal net charge should depend on the length of sequence [ [162] , [163] , [164] ].…”
Section: Approaches To Improve Biological Activities Of Ampsmentioning
confidence: 99%
“…There are several amino acids that have been extensively studied due to its striking impact on the structure or activity of antimicrobial peptides. Proline and Glycine provides more flexibility for the peptide structure, which can help induce the hemolytic activity [ 151 , 163 ]. Tryptophan (W) is demonstrated to facilitate the interaction with bacteria membrane when it was put in the interface between hydrophobic face and hydrophilic face of the amphipathic helices [ 151 , 161 , 167 ].…”
Section: Approaches To Improve Biological Activities Of Ampsmentioning
confidence: 99%
“…For example, a study demonstrated that, compared to the stapled heptapeptide 22, all of its dimeric analogs showed a substantial increase in antibacterial activity. 68 However, this does not always guarantee an enhancement in the antibacterial activity of stapled peptides when compared to that of the native unmodified analogs. For example, the stapled antimicrobial peptides in the work of Chapuis et stability and helical content.…”
Section: Application Of An All-hydrocarbon Stapling Approach For the ...mentioning
confidence: 99%
“…This suggested option may increase the size of the hydrophilic face (e.g., by replacing hydrophobic residues with polar cationic charged lysine 41 ) or induce an interruption of the hydrophobic face caused by hydrophilic residues. 85−87 Moreover, some modifications that aim to increase the conformational flexibility of stapled peptides have proven to be effective in reducing the hemolytic activity, such as introducing the "helix breaker" proline 68 or making the amino group at the N-terminus free instead of acetylated or succinylated. 44,55 Additionally, it has been suggested that when the tryptophan (W) residue is appropriately placed at the interface between the hydrophobic and hydrophilic faces it can facilitate the interaction between the AMP and the bacterial membrane.…”
Section: Application Of An All-hydrocarbon Stapling Approach For the ...mentioning
confidence: 99%